Konstruk Epistemologi Islam: Telaah bidang Fiqh dan Ushul Fiqh - Nirwan Syafrin (Universitas Darussalam Gontor, 2009)
Islamic Jurisprudence is a knowledge on the practical Islamic law based on its detailed approve concerning with the deeds of human. This article discusses on the position of Jurisprudence in relation with two different functions, indeed as a positive law and moral standard. In order to derive the Islamic law from its primary sources, al-Qur’an and the Sunnah, Islamic Jurisprudence needs theoretical tool and methodology which commonly named as the Principle of Islamic Jurisprudence. So the Islamic Jurisprudence is considered as Islamic epistemology which stands as the basis of the development of Islamic Jurisprudence as a knowledge. As the basis of epistemology, the principle of Islamic Jurisprudence is closely related to theology. Furthermore, this knowledge develops a principle on adillah which its foundation has been constructed by Syafi’i, indeed al-Qur’an, the Sunnah, Ijma’ and Qiyas. Since constructed by Syafi’i, this Principle of Islamic Jurisprudence has some changes and innovations. This innovation has been in the long duration of time with complicated problems and helped the ummah to solve the problems.